2019
DOI: 10.24874/jsscm.2019.13.01.02
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic performances improvement of NACA 4415 profile by passive flow control using vortex generators

Abstract: Improvement of the airfoil NACA 4415 aerodynamic performances by flow control using a passive technique was achieved in this study. Gothic-shaped vortex generators were added at the profile upper surface. Vortex Generators (VG) were used to avoid boundary layer separation at the profile trailing edge, thus reducing the drag force and improving aerodynamic performances. A numerical simulation with fluent code was performed. A parametric study was carried out to determine optimal disposition and dimensions of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…[1,2]. Hares et al [3] conducted a comprehensive investigation into the effects of passive flow control using vortex generators (VGs) on the aerodynamic performance of the NACA 4415 airfoil. Through simulations and parameter exploration, the authors identified optimal VG dimensions and positions, resulting in improved lift coefficients, particularly at high angles of attack.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2]. Hares et al [3] conducted a comprehensive investigation into the effects of passive flow control using vortex generators (VGs) on the aerodynamic performance of the NACA 4415 airfoil. Through simulations and parameter exploration, the authors identified optimal VG dimensions and positions, resulting in improved lift coefficients, particularly at high angles of attack.…”
Section: Introductionmentioning
confidence: 99%
“…Since the introduction of passive control through vortex generators by Taylor (1947), this technique has been widely used to delay boundary layer separation through parametric studies (Lin. 1999, Godard et al 2006, Zhen et al 2011, Fouatih et al 2016and Hares et al 2019, to improve the wings lift (Nickerson. 1986), avoid or delay separation in subsonic diffusers (Brown et al 1968) and reduce aircraft fuselage drag (Calarese et al 1985).…”
Section: Introductionmentioning
confidence: 99%